An Account Of Psychosocial Issues Among Syrian Students Attending Malaysian Public Universities - Rani, Uzma (2022)
The world has been facing events of war and conflicts since its modern conception. War destroys communities and families and often disrupts nations' social and economic fabric. The effects of war include long-term physical, social and psychological harm to the individuals. Any war could have severe impacts far beyond borders by forcing the population to migrate for good. Syrian war in 2011 created severe stress in the region resulting in the mass migration of people to the peaceful zones of the world to get a better life. Many young university-going students also migrated to achieve higher education, to make their future better and peaceful. The present study primarily aims at the Syrian university students to explore their life experiences during the conflict, their psychosocial issues, and their life management at this stage. This study also explores their opinion and suggestions as international students coming from war zones for the host country. In-depth interviews were conducted with fifteen (15) Syrian university students and three public universities in Malaysia. Clarke and Braun analyzed the data using NVivo 11 Pro and reflexive thematic analysis. Three main themes emerged from the interviews: psychological issues, social issues, and future concerns. It was discussed by the participants of the study that they are very positive regarding their future and paid gratitude to Malaysian people for their positive humanitarian attitude for their crisis.